2021
DOI: 10.3389/fonc.2021.769730
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Free Remission in Chronic Myeloid Leukemia and New Approaches by Targeting Leukemia Stem Cells

Abstract: The therapeutic landscape for chronic myeloid leukemia (CML) has improved significantly with the approval of tyrosine kinase inhibitors (TKIs) for therapeutic use. Most patients with optimal responses to TKIs can have a normal life expectancy. Treatment-free remission (TFR) after discontinuing TKI has increasingly become a new goal for CML treatment. However, TKI only “control“ CML, and relapse after discontinuation has become a key factor hindering patient access to attempt TFR. In this study, we reviewed stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 172 publications
1
16
0
Order By: Relevance
“…However, long‐term TKI use is frequently accompanied by adverse events, impact on quality‐of‐life (QoL), impaired mental health, poor adherence, and high treatment costs 2–4 . In recent years, several clinical trials and real‐world studies have shown that 40%–60% of patients with a sustained, stable deep molecular response (DMR) can successfully discontinue TKI and achieve treatment‐free remission (TFR) 5–7 . Currently, patients with more than 5 years of TKI and 3 years of DMR without prior treatment failure should be considered for withdrawal 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, long‐term TKI use is frequently accompanied by adverse events, impact on quality‐of‐life (QoL), impaired mental health, poor adherence, and high treatment costs 2–4 . In recent years, several clinical trials and real‐world studies have shown that 40%–60% of patients with a sustained, stable deep molecular response (DMR) can successfully discontinue TKI and achieve treatment‐free remission (TFR) 5–7 . Currently, patients with more than 5 years of TKI and 3 years of DMR without prior treatment failure should be considered for withdrawal 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, it has been observed that as many as half of the patients can achieve TFR after the discontinuation of a TKI treatment. Moreover, it is observed that molecular recurrence appears within 6 months after discontinuation [ 12 , 13 ]. Factors such as the disease itself or those related to the patient, such as immune status or persistence of CD26+ leukaemic stem cells, may influence the likelihood of achieving and maintaining a TFR.…”
Section: Discussionmentioning
confidence: 99%
“…They were not excluded from the analysis if they stopped having a response before 6 months. This period of follow-up was determined on the basis of several studies that showed that the incidence of molecular recurrence is highest in the first 6 months [ 12 , 13 ]. As the literature regarding their effectiveness on low-dose patients is more limited, all patients on low-dose TKIs were included, regardless of the duration of the dose.…”
Section: Methodsmentioning
confidence: 99%
“…The action of HIF-1 inhibitors associated with TKIs has been shown to reduce the survival and growth of cells in CML in murine models. The HIF-1 deletion has also been tested in in vivo and in vitro models and has been shown to inhibit CML proliferation, both without serious effects on HSCs (120)(121)(122).…”
Section: Treatment Perspectivesmentioning
confidence: 99%
“…Despite the large number of tests involving TKIs, medications and methodologies have also been developing as the case of Bortezomibe. Its function is based on decreasing the expression of CDK6, an important agent in the proliferation of LSCs (120,125,126).…”
Section: Treatment Perspectivesmentioning
confidence: 99%